Computational optimization of finite difference methods on the CM5 - Shearer, M.M. (Parallel computing, 1996)
Techniques used to optimize a finite-difference program on a Thinking Machines' CM5 parallel processing system are presented. These techniques are discussed within several categories: vector unit optimization, separation of communications and computations, and optimal data partitioning. A simplified model is employed to illustrate these concepts. The results of applying these techniques to a more complicated finite-difference calculation are also reported.